A Multidimensional Interdisciplinary Analysis of Ache Lhamo's Ritual Characteristics and Cultural Values (Journal of Global Arts Studies, 2025)
Background: As a traditional Tibetan performing art, Ache Lhamo integrates religious rituals and theatrical art, carrying profound cultural and religious values. In the process of modernization, its protection is faced with the contradiction between static preservation and dynamic development. Objective: From an interdisciplinary perspective, combining Victor Turner's ritual drama theory, Richard Schechner's restored behavior theory, and Laurajane Smith's cultural heritage theory, this paper analyzes the ritual characteristics, artistic inheritance, and cultural values of Ache Lhamo, so as to provide theoretical support and practical guidance for the sustainable development of traditional performing arts and the dynamic protection of intangible cultural heritage. Methods: Using interdisciplinary research methods, combined with ritual drama theory, restored behavior theory, and cultural heritage theory, this paper makes a multi-dimensional analysis of the ritual nature, artistic inheritance, and cultural value of Ache Lhamo. Results: Ache Lhamo transmits religious and social meanings through the combination of ritual and drama. Its core performing elements maintain the vitality of traditional culture and meet contemporary needs through restored behaviors in the context of modernization. As a cultural heritage, it is dynamic and needs to maintain its cultural function as a "living organism" through recreation. Conclusion: The dynamic transformation of Ache Lhamo is the key to its sustainable development, which provides theoretical and practical references for the protection and innovation of intangible cultural heritage.
Keywords: Ache Lhamo; Ritual Drama; Intangible Cultural Heritage; Dynamic Protection